Pendidikan Seksual Dalam Perspektif Hadits - Lubis, Zulfahmi; Asmadi, Soraya Zairina; luthfiah, izmi; Puteri, Aulia Rahmah; Asmiralda, Febrina (Journal Of Human And Education (JAHE), 2025)
This article aims to explain Sexual Education from a Hadith Perspective. The main focus of this research is to analyze the meaning of sexual education and what hadiths are related to sexual education. This type of research uses libraries (library research), namely a study used to collect information and data with the help of various kinds of library materials. The results of this research show and direct readers to know the meaning of sexual education and hadiths related to sexual education.